APPLICATION OF DIGITAL LEARNING IN STIMULATING LITERACY IN EARLY CHILDREN AT TKIT UMMUL QURO - Rochani Malawat; Sariyati; Nur Wahida; Srirejeki Mugilestari (International Conferences on Early Childhood Education Proceedings, 2024)
In the current digital era, technology has made things easier for society, making it easier for people to gain insight and knowledge through various platforms. The more advanced and developed technology is, the more it influences all aspects, including aspects of children's education. Parents and educators at schools are required to use technology to introduce literacy at an early age in learning. So educators must also apply digital literacy to learning. One of the digital learning media to increase understanding of digital literacy for young children is YouTube. The method used in this research is a qualitative descriptive research method. The population in this study were TKIT Ummul Quro Manokwari students. The sample in this study was 80 children, including 20 children in group A (aged 4-5 years) and 60 children in group B (aged 5-6 years). Based on research results through playing videos of the prophets' siroh, children's digital literacy skills increase in processing, processing and communicating information. Of the 80 children who listened to digital and non-digital literacy Siroh Nabi, the comparison was that those who listened to digital literacy were more than the non-digital ones. The implication of this research is that digital learning media can be used to stimulate early childhood literacy skills in PAUD institutions.